Language learning in conflictual contexts: a study of Turkish Cypriot adolescents learning Greek in Cyprus - Tum, Danyal Oztas; Kunt, Naciye; Kunt, Mehmet (Routledge Journals, Taylor & Francis Ltd, 2016)
The Turkish Cypriot and Greek Cypriot communities in Cyprus have been divided for the last five decades. This study investigated whether the recent introduction of Greek language studies in Turkish Cypriot secondary schools affects students' attitudes towards the language, its speakers and culture, and motivation to study the language. Findings revealed that students studying Greek (experimental group) report having more positive attitudes towards Greek, its culture, and speakers and are more motivated to study it. Findings confirm the important role the degree of satisfaction with language studies plays in students' motivation to study a language.
Keywords: language minorities; Language attitudes; policy issues